High Prevalence and High Rate of Antibiotic Resistance of Mycoplasma genitalium Infections in Men Who Have Sex With Men: A Substudy of the ANRS IPERGAY Pre-exposure Prophylaxis Trial. (11th December 2020) - Berçot, Béatrice; Charreau, Isabelle; Rousseau, Clotilde; Delaugerre, Constance; Chidiac, Christian; Pialoux, Gilles; Capitant, Catherine; Bourgeois-Nicolaos, Nadège; Raffi, François; Pereyre, Sabine; Le Roy, Chloé; Senneville, Eric; et al.
Abstract: Background: Mycoplasma genitalium (MG) is an emerging pathogen among men who have sex with men (MSM) with raising rates of antibiotic resistance. This study assessed the prevalence and incidence of MG infection in MSM enrolled in the open-label phase of the ANRS IPERGAY trial with on-demand tenofovir disoproxil fumarate/emtricitabine for human immunodeficiency virus prevention and the impact of doxycycline post-exposure prophylaxis (PEP). Methods: 210 subjects were tested at baseline and at 6 months by real-time PCR assays for MG detection in urine samples and oropharyngeal and anal swabs. Resistance to azithromycin (AZM), to fluoroquinolones (FQs), and to doxycycline was investigated in the French National Reference Center of Bacterial Sexually Transmitted Infections (STIs). Results: The all-site prevalence of MG at baseline was 10.5% (6.3% in urine samples, 4.3% in anal swabs, 0.5% in throat swabs) and remained unchanged at 6 months whether or not PEP was used: 9.9% overall, 10.2% with PEP, 9.6% without. The overall rate of MG resistance (prevalent and incident cases) to AZM and FQs was 67.6% and 9.1%, respectively, with no difference between arms. An in vivo mutation of the MG 16S rRNA, which could be associated with tetracycline resistance, was observed in 12.5% of specimens tested. Conclusions: The prevalence of MG infection among MSM on pre-exposure prophylaxis was high and its incidence was not decreased by doxycycline prophylaxis with a similar high rate of AZM and FQ resistance, raising challenging issues for the treatment of this STI and supporting current recommendations to avoid testing or treatment of asymptomatic MG infection. Abstract : The prevalence of Mycoplasma genitalium infection among men who have sex with men on pre-exposure prophylaxis was high; its incidence was not decreased or increased by doxycycline prophylaxis with a similar high rate of azithromycin and fluoroquinolone resistance, raising challenging issues for the treatment of this sexually transmitted infection.